Technology Acceptance Model of ATM Machine Services: A Case Study of MyGraPARI within Analytical Hierarchy Process - Sutresno; Achmad Affandi (Airlangga Journal of Innovation Management, 2023)
Determining the priority level of acceptance of the MyGraPARI ATM machine service technology at Jam Gadang Bukit Tinggi is crucial for enhancing user satisfaction and streamlining financial transactions. The implementation of the Analytic Hierarchy Process (AHP) framework can effectively identify and prioritize factors that influence user acceptance and satisfaction. AHP systematically decomposes the decision-making process into a hierarchical structure, enabling the evaluation of various criteria based on their relative importance. AHP quantifies the subjective judgments of decision-makers, resulting in a comprehensive understanding of the factors that drive user acceptance and satisfaction. This predictive capability enables decision-makers to select the most effective strategies, optimizing the overall user experience and maximizing the adoption of MyGraPARI ATM machines at Jam Gadang Bukit Tinggi. In conclusion, the application of the AHP method is highly relevant and beneficial for overcoming existing challenges and enhancing the value proposition of MyGraPARI ATM machines. By prioritizing critical factors, implementing targeted strategies, and evaluating the impact of improvement efforts, AHP empowers decision-makers to optimize user acceptance and satisfaction, leading to a more successful and impactful MyGraPARI ATM service at Jam Gadang Bukit Tinggi.